From Crisis Mode to Choice: Factors Influencing Student Satisfaction with Online Education - State, Olimpia; Tanase, Mihail Ovidiu; Iorgulescu, Maria Cristina; Gheorghe, Georgica (Transformations In Business & Economics, 2026)
This study examines undergraduate students’ satisfaction with online learning compared to traditional teaching at a Romanian economic university. Using survey data from 313 students collected between April 2022 and March 2023, the research analyzes satisfaction levels, perceived challenges, and key predictors influencing the online learning experience. Results indicate generally high satisfaction, frequent use of audio-video platforms, and strong recognition of cost savings, although some students reported technological barriers, workload pressure, and emotional difficulties. Regression analyses reveal a bidirectional relationship between satisfaction and preference for online learning, and underscore the importance of institutional quality, prompt feedback, and acceptance of online learning as the “new normal.” The S.T.A.R. factors– technical competency, additional assignment time, teacher preparedness, and time-management challenges – account for a significant portion of satisfaction variance. The study concludes that effective online learning depends on the alignment of student skills, instructor readiness, and institutional support.
Keywords: Higher Education; online learning; human resource; Romania